Comparative transcriptome analysis of shortened fruit mutant in woodland strawberry (Fragaria vesca) using RNA-Seq - Shou-ming WANG; Wei-jia LI; Yue-xue LIU; He LI; Yue MA; Zhi-hong ZHANG (Journal of Integrative Agriculture, 2017)
Genes controlling fruit appearance determine fruit shape and size. In ethylmethane sulfonate (EMS)-mutagenized lines of Fragaria vesca accession Yellow Wonder (YW), two fruit shapes are observed: wild-type long fruit and mutated shortened fruit (sf). In this study, we first characterized sf based on morphology, histology, cytology and physiology. The sf was identified as a gibberellin (GA)-deficient mutant, and four complementary DNA (cDNA) libraries separately constructed from flower buds and small green fruits of YW and sf were sequenced to comparatively analyze transcriptome differences. A total of 29 differentially expressed GA pathway genes were identified by comparisons between YW1 and sf1, and 28 differentially expressed GA pathway genes were identified between YW2 and sf2. In addition, the expression patterns of 45 differentially expressed genes were validated by quantificational real-time PCR (qRT-PCR), and the results were highly concordant with the RNA-Seq results. This transcriptome analysis provides valuable information for understanding the molecular mechanisms of fruit development of strawberry.